The Multi-Faceted Concept of Transparency - Jens Forssbæck; Lars Oxelheim (Research Institute of Industrial Economics (IFN), 2014)
Transparency has become a catchword and in the economic-political debate is often seen as a universal remedy for all sorts of problems. In this paper, we analyze and discuss the meaning and use of the concept of transparency in economic research. We look for common denominators across different areas where the concept is used, and find that transparency in essence is about reductions in information asymmetries, and therefore entails the transfer of information from a sender to a receiver. Transparency goes beyond mere information disclosure in that it has a demand-side dimension: the information transferred should be trustworthy and have a value to the receiver. We emphasize the distinction between ex ante transparency - related to predictability - and ex post transparency - related to accountability. In economics, increased transparency is mostly rationalized on grounds of improving efficiency, but sometimes transparency is properly viewed simply as a right to know. Complementarities between different types of transparency are pervasive, and its causes and effects typically co-determined - i.e. transparency is endogenous. As a means to improve competitiveness and economic growth, transparency of economic policy and corporate as well as institutional transparency interact. We challenge the view that more transparency is always better and argue for concave net benefits and the existence of optimal transparency, but optimality varies across policy areas, institutional settings, industries and individual firms.
Keywords: D82; E24; E27; E37; E52; E58; E62; G38; M10; 330; Asymmetric Information; Transfer of Information; Moral Hazard; Adverse Selection; ransparency; Optimal Transparency; Ex Ante Transparency; Ex Post Transparency; Predictability; Accountability; Economic Policy; Economic Growth